The relationship of rural tourism with sustainable tourism and outdoor activities: a bibliometric analysis - Ferreira, Jessica (2022)
A bibliometric study is a method used to evaluate the productivity of scientific results in quantitative terms. Bibliometricians apply mathematical and statistical methods to quantify scholarly communications. Using the Bibliometrix program, a database compiled from SCOPUS and Web of science was studied to study the different scientific and literary behaviours of rural tourism development, tourism sustainability, and outdoor activities. In the main database steps, 161 articles were analysed, of which 61 were SCOPUS articles, and 100 were Web of Science articles. As per this database, the relationship between rural tourism with sustainable tourism and outdoor activities, through a bibliometric analysis, looks to study the annual scientific production, the research impact, the authors, and articles most relevant to the themes of research trends over the years. Several interesting and important conclusions were obtained from these results for developing the themes. The results of this study indicate that sustainable tourism and rural tourism have extreme relevance to the studies carried out. Hence, rural tourism and outdoor activities are increasingly sustaining a relationship of partnership, much due to the influences of COVID-19.